A Sociolinguistics Analysis of Stereotypes in the Freedom Writers Movie - Puspitasari, Lintang Putri; Nugroho, Abdillah (International Journal of Language and Literature, 2023)
Stereotypes are viewed negatively since they indicate negative preconceptions about others. Hence, stereotypes are important to study because people might unknowingly employ stereotypes about others in regular encounters. Stereotypes are also found in many films, one of which is in the film "Freedom writer." The aims of this study are to analyze the categories of stereotypes that existed in the film Freedom Writer and to identify the functions of the stereotypes that are produced in the film. The researcher uses descriptive qualitative research. This research is a sociolinguistic approach of stereotypes occurring in the movie entitled Freedom Writers. The data is all utterances in the movie. The data analysis technique is carried out by employing sociolinguistics theory. The results of this study show that there are three categories of stereotypes occur: gender, race, and physical traits. The characters in Freedom Writers represent a diverse range of races, and their frequent interactions enable them to readily observe the different characteristics associated with their respective races. Consequently, due to the film's setting in a multicultural society, various stereotypes regarding race, with a particular emphasis on conflicts related to skin color, are prevalent. These stereotypes are influenced by cultural factors within this context.